Book Review: Dariusz Grala, "The Security of Military Supply Chains" [“Bezpieczeństwo wojskowych łańcuchów dostaw”], Academy of War Studies Publishing House, Warsaw 2024, ISBN 978-83-8263-503-4, pp. 326. - Zamelek Paulina (2024)
A new monograph titled "The Security of Military Supply Chains" has emerged in the publishing market, released in 2024 by the Academy of War Studies Publishing House (ISBN 978-83-8263-503-4). This publication spans 326 pages and represents a significant contribution to Polish scientific literature, as the subject matter has not been analysed in such a comprehensive manner until now. The Author of the book is Dariusz Grala, a Colonel in the Polish Army, a Doctor of Engineering, and the current Dean of the Faculty of Management and Command at the Academy of War Studies. The monograph introduces the reader to an extensive, erudite discourse at the intersection of political science research, security studies, and management and quality. The Author meticulously and logically discusses areas related to the security of military supply chains, which have previously been underexplored in the literature. The term "security" is understood here in various contexts, encompassing both states and processes that influence military supply chains. The Author highlights their role as a set of cooperating structures aimed at delivering goods essential for the execution of military training operations, operational activities, and combat missions. The literature often encounters the term "defence sector supply chains"; however, in the military context, the perspective on the functioning of these supply chains has a broader and often sensitive significance. This "sensitive" nature of the security of military supply chains —understood from the intentions expressed in the Introduction — has become the subject of the Author's research, which integrates theories and practices from military logistics and supply chain management. The considerations focus on the processes occurring within these chains under various conditions. This approach is particularly important in the realm of security and defence, as civil supply chain publications often overlook, assuming it to be self-evident, the specific security considerations related to military needs. This publication, in a sense, bridges these two worlds.